Delivery of Eye and Vision Services in Aboriginal and Torres Strait Islander Primary Healthcare Centers - Burnett, Anthea M.; Morse, Anna; Naduvilath, Thomas; Boudville, Andrea; Taylor, Hugh R.; Bailie, Ross (Frontiers in Public Health, 2016)
Background Routine eye and vision assessments are vital for the detection and subsequent management of vision loss, which is particularly important for Aboriginal and Torres Strait Islander people who face higher rates of vision loss than other Australians. In order to guide improvements, this paper will describe patterns, variations, and gaps in these eye and vision assessments for Aboriginal and Torres Strait Islander people. Methods Clinical audits from 124 primary healthcare centers (sample size 15,175) from five Australian states and territories were conducted during 2005–2012. Main outcome measure was adherence to current guidelines for delivery of eye and vision assessments to adults with diabetes, those without a diagnosed major chronic disease and children attending primary healthcare centers. Results Overall delivery of recommended eye and vision assessments varied widely between health centers. Of the adults with diabetes, 46% had a visual acuity assessment recorded within the previous 12 months (health center range 0–88%) and 33% had a retinal examination recorded (health center range 0–73%). Of the adults with no diagnosed major chronic disease, 31% had a visual acuity assessment recorded within the previous 2 years (health center range 0–86%) and 13% had received an examination for trichiasis (health center range 0–40%). In children, 49% had a record of a vision assessment (health center range 0–97%) and 25% had a record of an examination for trachoma within the previous 12 months (health center range 0–100%). Conclusion There was considerable range and variation in the recorded delivery of scheduled eye and vision assessments across health centers. Sharing the successful strategies of the better-performing health centers to support focused improvements in key areas of need may increase overall rates of eye examinations, which is important for the timely detection, referral, and treatment of eye conditions affecting Aboriginal and Torres Strait Islander people, especially for those with diabetes.